2009
DOI: 10.1111/j.1551-2916.2009.03075.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Particle and Agglomerate Size on the Elastic Moduli of Porous Yttria (Y2O3)

Abstract: The present study shows the effect of porosity on the dynamic elastic moduli of partially dense yttria (Y2O3). This article reveals that the sound velocities and the elastic moduli of the porous samples depend not only on density, but also upon the reciprocal of the initial particle and agglomerate size. These findings explain some of the variation in the elastic moduli found especially, but not only, for highly porous yttria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…These values are similar to, and within the uncertainties of, published data 11,12 . For example, for high‐density Y 2 O 3 , Desmaison‐Burt et al 12 reported a value of 176 GPa; for fully density Y 2 O 3 , Yeheskel et al recently reported a value of 180.4 ± 4.1 GPa, Poisson's ratio in both studies was ≈0.30 12,40 …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…These values are similar to, and within the uncertainties of, published data 11,12 . For example, for high‐density Y 2 O 3 , Desmaison‐Burt et al 12 reported a value of 176 GPa; for fully density Y 2 O 3 , Yeheskel et al recently reported a value of 180.4 ± 4.1 GPa, Poisson's ratio in both studies was ≈0.30 12,40 …”
Section: Resultssupporting
confidence: 85%
“…The velocities were measured using a pulse–echo method described elsewhere 11 . The sample's density (ρ) was measured using Archimedes' principle 40 . The uncertainty in the density measurements is estimated to be ≈± 0.1%; that in V L ≈± 0.4% and for V T ≈± 0.25%.…”
Section: Methodsmentioning
confidence: 99%
“…40 The sample's density, ρ, was measured using Archimedes' method. 41 The uncertainty in the density measurements is estimated to be ≈±0.1%; that in V L ≈ ±0.1%, and that in V T ≈ ±0.1%. The resulting uncertainty in E S is thus better than 1%, while that of the dynamic Poisson's ratio, ν S , is about 3%.…”
Section: Dynamic Elastic Modulimentioning
confidence: 99%
“…The temperature of calcination must be sufficiently high for gas desorption but low enough to prevent particle agglomeration. The latter reduces the surface area of the powder and, thereby, the early‐stage driving force for sintering . Adding a low temperature, pre‐heating stage to the sintering procedure can remove a significant fraction of the residual surface water on the green‐body, thereby facilitating improved densification.…”
Section: Introductionmentioning
confidence: 99%
“…The latter reduces the surface area of the powder and, thereby, the early-stage driving force for sintering. 34 Adding a low temperature, pre-heating stage to the sintering procedure can remove a significant fraction of the residual surface water on the green-body, thereby facilitating improved densification. However, proper choice of both the powder calcination and the green body pre-heating temperatures is critical.…”
Section: Introductionmentioning
confidence: 99%